La identidad social en la educación: hacia una participación ciudadana - Guanipa Ramírez, Luis F. (2020)
As a process of human interaction, society has explored different perspectives in its multidimensional approach, and it might be argued that this has influenced education as a social, historical and citizenship issue, subject to economic, political and social models that have been developed across the world, giving rise at every stage in the history of humankind to a new educational molding force for individuals, and the development of human identity. Social identity is seen as the sense of belonging to society experienced by the individual, through the adopting of behaviors and ways of thinking which significantly influence the formation of civic values, particularly with regard to participation in civic decision making.